Confirmation of causality of climatic and soil physical factors affecting the corn (Zea mays L.) yield for silage in the climate-soil-yield network - Kim Moonju (Agriculture, 2023)
This study aimed to confirm the causality of climatic and soil physical factors on silage corn yield based on the climatesoil-yield network in Korea. The climatic variables were growing degree days, high temperature, low temperature, surface temperature, rainfall, relative humidity, wind speed, and sunshine duration before and after silking. The soil physical variables were the effective depth, slope and drainage class of the soil. The yield variables were total digestible nutrients, dry matter and fresh matter yields. The network was constructed using structural equations and neural network models. In the result of the network, three causalities were remarkable. First, all longitudinal climatic causality before and after the silking stages were significant. It implies that the effect of climate in the vegetative stage reaches to yield through themselves in the reproductive stage. Second, there was the causality between climatic and soil physical factors based on indirect effects. Thus, it is likely to lead to an offset between the direct and indirect effects of soil physical factors. Finally, the effects of drought and heavy rainfall were clear before and after silking stages, respectively. It indicates that stress can damage the corn yield for silage. Here, the damage caused by the drought could be recovered due to various indirect effects, while the damage caused by heavy rainfall was fatal because there was a lack of an indirect path to recover from. This study contributed to identifying how various climatic and soil physical factors can affect production in the network. Furthermore, the climate-soil-yield network for silage corn in this study will help extend the structure with various factors in future studies.